Ficus benghalensis extract mediated green synthesis of silver nanoparticles, its optimization, characterization, computational studies, and its in vitro and in vivo biological potential - Inam Ud Din; Rahaf Ajaj; Abdur Rauf; Zubair Ahmad; Naveed Muhammad; Shahid Ali; Hassan A. Hemeg; Imran Ullah (PLoS ONE, 2025)
In this work, Silver (Ag) nanoparticles (NPs) were synthesized via green synthesis using Ficus benghalensis root extract (FBRE), serving as a capping and stabilizing agent. The synthesized Ag NPs were characterized via complementary characterization techniques, including SEM, XRD, EDS, UV-Vis, and FT-IR. SEM analysis revealed the fabrication of spherical NPs with an average size of 41.55 nm. A plasmon resonance peak was observed at 430 nm. FBRE effectively capped and stabilized the Ag NPs, ensuring their structural integrity over time, and is confirmed via FT-IR scan. DFT calculation revealed a thermodynamically and mechanically stable system. Moreover, optoelectronic properties confirmed the metallic behavior of Ag with a major contribution from 4d orbital near the fermi level and 5s orbital contribution to the conduction band with light absorption in the visible spectrum. Biological evaluations demonstrated significant enzyme inhibition. Ag NPs inhibited urease (80.76%), α-glucosidase (80.98%), carbonic anhydrase II (89.32%), and xanthine oxidase (49.9%), outperforming FBRE. In Vivo, Ag NPs exhibited dose-dependent analgesic (83.09% writhing inhibition at 10 mg/kg, similar to diclofenac) and sedative (16.09% locomotor reduction at 10 mg/kg) effects. Molecular docking confirmed strong enzyme-ligand interactions. These findings highlight the biomedical potential of FBRE-synthesized Ag NPs, particularly for enzyme inhibition and pharmacological applications.